Isolation and Preliminary Characterization of Temperature-Sensitive Mutants of Rhizobiophage C - Atkins, Gregory J. (1973)
By using mutagenesis induced by N-methyl-N′-nitro-N-nitrosoguanidine, 150 temperature-sensitive mutants of rhizobiophage c were isolated. All were able to form plaques at 14 C but not at 29 C. They were classified into 21 complementation groups. Representative temperature-sensitive mutants from each complementation group were analyzed with regard to gene function. The approximate time of expression of the genes defined by the mutants was measured by temperature-shift experiments. Most genes began to be expressed at 4.0 to 7.5 h after infection at 14 C. Four genes were found which were expressed 2.5 to 3.5 h after infection. Some mutants showed no DNA synthesis at 29 C; some showed a delay in lysis. Some produced apparently normal particles after infection and lysis at 29 C; others produced various types of defective particles. Some mutants showing no DNA synthesis at 29 C nevertheless caused lysis at the normal time together with the production of phage structural components. Representative mutants from each complementation group were mapped by using two-factor crosses. A preliminary genetic map of phage c was constructed from the data.